Export activities under financial constraints: Margins, quantities and prices - Angelo Secchi; Federico Tamagni; Chiara Tomasi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
This paper provides a comprehensive analysis of the role that financial constraints play in shaping firms' export activities. We use custom information on cross borders transactions for Italian firms, together with an informative measure of financing constraints based on an official credit rating issued by an independent institution. Controlling for potential selection bias our results confirm that limited access to external capital narrows the scale of foreign sales, the exporters' product scope and the number of trade partners. We enrich previous analyses showing that financial problems influence firms' strategies of switching among products or destinations, and also affect firms' pricing decisions. Constrained firms have a reduced probability of adding new products or destinations and a higher probability of dropping products or destinations. Moreover, they attempt to offset, via higher prices, the negative impact on foreign revenues induced by the decreased physical quantity associated with financial constraints.
Keywords: F10; F14; F30; G20; 330; financial constraints; margins of export; export prices